MANAJEMEN INOVASI : PROMOSI DALAM MENDUKUNG SISTEM MERIT DI BKD PROVINSI JAWA BARAT - Wibowo, Galih; Soeprihattanto, R. Bambang (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
To realize World Class Government, the concept of management of civil servants must innovate, including in terms of employee promotion. The West Java Provincial Government has become one of the regional governments that has carried out many bureaucratic reforms and staff management innovation, including the implementation of promotions through open selection. Problems that arise, the phenomenon of promotion or open selection implemented with a diverse system in each local government. Reviewing employee promotion patterns in West Java can be an illustration of the impacts and solutions that have emerged in the management of promotional innovations. Through the analysis of basic indicators of law, policy and intervention, technology implementing, apparatus competencies, participants, procedural strategies, and financial resources, obtained a common thread the impact of employee promotion innovation management. Based on observations and discussions, the results were drawn to illustrate that the implementation was running well, but the need for regional legal products as the basis for implementing promotional innovation management policies, and integrated information technology development also electronic-based supervision and financial politics